PEMENUHAN HAK-HAK OLEH NEGARA TERHADAP PEKERJA MIGRAN INDONESIA NON-PROSEDURAL PASCA PRAKTIK HUMAN TRAFFICKING DI MYANMAR TAHUN 2022-2023 BERDASARKAN PALERMO PROTOCOL: Fulfillment of Rights by the State towards Non-Procedural Indonesian Migrant Workers Post Practices of Human Trafficking in Myanmar 2022-2023 based on the Palermo Protocol - Difasyah Halilintar Sumadikara; Aji Wibowo (Faculty of Law, Universitas Trisakti, 2025)
The practice of human trafficking is a form of modern slavery that can threaten state sovereignty and human rights which are regulated in the International Protocol to Prevent, Suppress and Punish Trafficking in Persons or the Palermo Protocol, this practice of human trafficking occurs among vulnerable parties including migrant workers as has happened to dozens non-procedural Indonesian migrant workers in Myanmar in 2022-2023. The formulation of the problem is what forms of human rights violations experienced by non-procedural Indonesian migrant workers in connection with the practice of human trafficking in Myanmar and how the Indonesian government is trying to fulfill the rights of non-procedural PMIs after the practice of human trafficking in Myanmar in 2022-2023 based on Palermo Protocols. This type of research is normative, descriptive research and drawing conclusions using deductive logic. As a result, non-procedural PMI who experience human trafficking practices in Myanmar experience a form of violation of human rights in the provisions of International Human Rights Law such as the right to life, the right to freedom, the right not to be tortured, the right not to be forced to work and other rights. Efforts made by the government Indonesia in fulfilling the non-procedural rights of PMI after the practice of human trafficking in Myanmar is the recovery of victims by legal processing of traffickers based on Law No. 21 of 2007 concerning trafficking in person to pay restitution and compensation, restore the psychological and traumatic conditions of victims in RPTC, carry out socialization by forming a trafficking in person Task Force, BP2MI, LPSK as well as collaboration with IOM, ASEAN and other countries.